PERILAKU HARIAN ORANGUTAN KALIMANTAN (Pongo pygmaeus) DI KAWASAN HUTAN KONSERVASI PT. KAYUNG AGRO LESTARI (KAL) KABUPATEN KETAPANG - Herwandi, Budi; Prayogo, Hari (JURNAL HUTAN LESTARI, 2018)
Indonesia is one of the countries that has 20% of the world's primate species, one of the primate species is an orangutan. This study aims to determine the behavior of Kalimantan orangutan (Pongo pygmaeus). The research was conducted in Conservation Forest Area, PT. Kayung Agro Lestari (KAL), Ketapang District. This observation was conducted by using focal animal sampling method on three individual orangutan found in conservation forest area with different age and sex. The three individual orangutan were observed in the morning after the orangutan got up and out of their nest until the orangutan made their nests late in the evening. The data of orangutan behavior is recorded with a duration of time every two minutes.Adult orangutan observed in conservation forest areas spend more time resting, followed by moving and eating activities, this behavior is different from younger orangutan who engage in more eating, moving and resting activities.. The observed orangutan do a lot of activities in the morning and afternoon, while in the daytime activities are mostly done is a rest activity.Keywords: Behavior Of Orangutan, Concervation Forest, Pongo pygmaeus.Indonesia is one of the countries that has 20% of the world's primate species, one of the primate species is an orangutan. This study aims to determine the behavior of Kalimantan orangutan (Pongo pygmaeus). The research was conducted in Conservation Forest Area, PT. Kayung Agro Lestari (KAL), Ketapang District. This observation was conducted by using focal animal sampling method on three individual orangutan found in conservation forest area with different age and sex. The three individual orangutan were observed in the morning after the orangutan got up and out of their nest until the orangutan made their nests late in the evening. The data of orangutan behavior is recorded with a duration of time every two minutes.Adult orangutan observed in conservation forest areas spend more time resting, followed by moving and eating activities, this behavior is different from younger orangutan who engage in more eating, moving and resting activities.. The observed orangutan do a lot of activities in the morning and afternoon, while in the daytime activities are mostly done is a rest activity.Keywords: Behavior Of Orangutan, Concervation Forest, Pongo pygmaeus.